Interactive Multimedia Development in Learning of Film Review Text for 8th Grade Students in Senior High School (SMP) 1 Tanjungmorawa - Eva Lindasari; Khairil Ansari; Marice Marice (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to produce interactive multimedia development in learning of film review text for 8th grade students in Senior High School (SMP) 1 Tanjungmorawa. The research method uses Research and Development method which refers to the development of the Borg and Gall which was modified by Sugiyono. The results of the validation of material experts on the feasibility of the content obtained an average of 90.7% in the category of "Excellent" aspects of the feasibility of the language obtained an average of 100% with the category of "Excellent".  For the assessment of the results of interactive multimedia validation by media experts an average of 84.7% with the category of "Excellent". Product trials are carried out in two stages: small group trials and limited field trials. Small group trials obtained an average percentage of 86.6 with the "Excellent" category. Limited field trials received an average percentage of 88.4 in the "Excellent" category. The effectiveness of teaching materials is obtained through student learning outcomes in the pretest and posttest. average score at pretest 44 and at posttest 77. This proves that interactive multimedia is feasible, easy, and effective for 8th grade students in Senior High School (SMP) 1 Tanjungmorawa.